2017
DOI: 10.1109/tkde.2017.2719026
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimal Connectivity on Multi-Layered Networks

Abstract: Networks are prevalent in many high impact domains. Moreover, cross-domain interactions are frequently observed in many applications, which naturally form the dependencies between different networks. Such kind of highly coupled network systems are referred to as multi-layered networks, and have been used to characterize various complex systems, including critical infrastructure networks, cyber-physical systems, collaboration platforms, biological systems and many more. Different from single-layered networks wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…As this research field deepened, scholars found that many systems in the real world have complex and highly interdependent structures, and single-layer networks are unable to address the problem of the cross-fusion of multiple systems; therefore, multi-layer network research gradually started attracting more and more attention [32,33]. Each layer in the multi-layer network represents a system or a subsystem, and the connection between the networks is realized based on the relationship between the actual system's layers [34,35]. Each layer in the multi-layer network may exhibit different local and global structural characteristics than those in the single-layer network, which provides an effective method for analyzing the interaction between different systems and the formation mechanism of the network [36][37][38].…”
Section: Multi-layer Networkmentioning
confidence: 99%
“…As this research field deepened, scholars found that many systems in the real world have complex and highly interdependent structures, and single-layer networks are unable to address the problem of the cross-fusion of multiple systems; therefore, multi-layer network research gradually started attracting more and more attention [32,33]. Each layer in the multi-layer network represents a system or a subsystem, and the connection between the networks is realized based on the relationship between the actual system's layers [34,35]. Each layer in the multi-layer network may exhibit different local and global structural characteristics than those in the single-layer network, which provides an effective method for analyzing the interaction between different systems and the formation mechanism of the network [36][37][38].…”
Section: Multi-layer Networkmentioning
confidence: 99%
“…The study of network robustness not only has been extended to many different network types, including weighted networks [97], network of networks [95], [96], [181], [182], interdependent networks [89], [92], [94], [183], [184], and multiplex networks [185], [186], but also has been applied to more and more real-world applications, for example land and air transport networks [24], [25], [187]- [194], wireless sensor networks [22], [77], [195], power grids [23], [196], [197], Internet of Things [198], and so on.…”
Section: E Real-world Applicationsmentioning
confidence: 99%
“…Prediction and inference of reality that has happened before is the basic function of forecasting models, while DTs can further forecast the extended reality by predicting facts that have never happened before. For example, [340] propose a disaster city DT for enhancing disaster response and emergency management processes, where disasters that have never happened before are simulated and real world systems are extensively forecast to enable increased visibility into network dynamics of complex disaster management and humanitarian actions. The digital twining of complex networked systems are also featured with a decision-making feedback loop with dynamically updated asset specific computational models infused [330].…”
Section: Volume X 20xxmentioning
confidence: 99%